ANALYSIS OF FINANCIAL LITERACY THROUGH THE USE OF SOCIAL MEDIA TOWARD FINANCIAL INCLUSION IN MSMES IN MALANG CITY - Ana Pralisti; Dias Satria (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a key focus of Indonesia’s economic development efforts. In Malang City, while financial inclusion has reached 86.53%, the level of financial literacy remains relatively low at 69.43%. This study explores how both general and digital financial literacy, along with the use of digital payment systems, affect MSMEs' ability to access formal financial services. It also examines the influence of social media in shaping the relationship between financial literacy, digital literacy, digital payment usage, and financial inclusion among MSMEs in the region. Furthermore, the research assesses whether social media acts as a moderating variable in these relationships. Adopting a quantitative research design, data were collected from 380 MSME owners through a structured questionnaire and analyzed using the Smart PLS (Partial Least Squares) method. The findings indicate that general financial literacy, digital financial literacy, and digital payments significantly contribute to enhancing financial inclusion, thereby improving MSMEs' access to formal financial services. However, the moderating role of social media remains limited, suggesting the need for more strategic and effective social media engagement to better integrate digital competencies, financial literacy, and digital payment practices. Ultimately, this research provides valuable insights into strengthening MSMEs and introduces a digital finance framework to advance financial inclusion.